DEVELOPING MORAL SELF-AWARENESS IN ADOLESCENCE: A PROGRAM-BASED THEORETICAL MODEL - Mamanazarov, Uchqun (Research Focus International Scientific Journal, 2026)
This article analyzes the development of moral self-awareness in adolescence and proposes a program-based theoretical model for its formation in educational and counselling contexts. Adolescence is a sensitive developmental stage in which self-evaluation, identity search, emotional instability, peer influence, and value testing become especially intensive. Under these conditions, moral development should be understood not as passive acceptance of rules but as the progressive formation of an inner ethical position. The paper conceptualizes moral self-awareness as a multicomponent construct that includes cognitive, emotional, reflective, communicative, and behavioral dimensions. Drawing on the author’s publications and related CIS and international research, the article argues that effective developmental programs must combine self-reflection, ethical reasoning, empathy-building exercises, guided discussion, psychological support, and situation-based training. The article presents the structure of such a program, identifies the pedagogical and psychological conditions of its success, and explains why moral self-awareness should be cultivated through active participation rather than lecture-based moralization. The conclusion is that adolescence-oriented programs are most effective when they integrate moral dialogue, reflective techniques, group interaction, and individualized counselling support within a culturally meaningful educational environment [1; 2; 3; 4].